Pediatric bone marrow transplantation: Psychopathologic features in recipients along with siblings. Issue 10 (8th August 2019) - Erden, Semih; Kuşkonmaz, Bülent Barış; Çetinkaya, Duygu Uçkan; Ünal, Fatih; Özsungur, Berna
Abstract: Objective: To analyze the development of psychopathology in recipients along with their donor and nondonor siblings and the relationship with the bone marrow transplantation (BMT) process. Methods: All children were interviewed using the Kiddie Schedule for Affective Disorders and Schizophrenia to assess psychopathology. The depression and anxiety symptoms and self‐esteem of children and adolescents were evaluated using the Children's Depression Inventory, State‐Trait Anxiety Inventory for Children, State‐Trait Anxiety Inventory, and Rosenberg Self‐Esteem Scale. Results: In this study, the depressive symptom level was found significantly higher in the donor group compared with the nondonor group. State anxiety symptoms were higher in the BMT group ( P < .05). There were no significant differences in trait anxiety symptoms. Self‐respect was higher in children in the donor group compared with those in the BMT group ( P < .05). During the transplant process, children with bone marrow transplants had a higher prevalence of depression, anxiety disorder, and attention‐deficit/hyperactivity disorder, and nondonor siblings had a higher prevalence of depressive disorder, anxiety disorder, and attention‐deficit/hyperactivity disorder compared with society in general. Conclusion: Physicians should deal with the family as a whole, not just their patient, and should be aware of the psychiatric risk of other siblings during the assessment.